The Indian Seaweed Resource: Their Nutritive Importance to Human Beings and Threats - Temkar, G. S.; Bhatt, A. J.; Joshi, Arti (International Journal of Bio-resource and Stress Management, 2018)
Seaweeds were the microalgae observed along the coastal ocean waters. They were observed near the coastal waters, mostly attached to any substratum. Ecologically they provides living and feeding habitat to the most of the aquatic animals. They are of three types-green, brown and red seaweeds. For human population they are useful for various purposes like food, fertilizers, medicines etc. In the present review article, reported studies from Indian as well as different waters throughout the world were discussed. Overall it was stated that, there was good amount of proximate and minerals composition of some scrutinized seaweed species, so in future it can be considered as food resource. The mineral and proximate composition comparison with terrestrial vegetables plants varieties reports, the good amount of these components in some of the analyzed seaweed species. Presently, the concept of Seaweed Aquaculture is one of the option to increase the seaweed production from country, but the unsuitable environmental and coastal oceanic conditions limits to such activities. To overcome this problem proper study were required and at the moment CMFRI, CSMCRI, NIO, etc. like institutes were came forward and they led research for the development of Seaweed Aquaculture. So this review article describe the importance of seaweeds for future generations as food as well as their medicinal importance, also explains status of the seaweed diversity along the Indian coast. The description about their threats represents how to take control measures over the seaweed cultivation, which will be useful for future seaweed cultivation prospective.